2014
DOI: 10.7575/aiac.ijels.v.2n.1p.52
|View full text |Cite
|
Sign up to set email alerts
|

Field Dependence/Independence Cognitive Styles: Are They Significant At Different Levels Of Vocabulary Knowledge?

Abstract: Cognitive styles influence the performance of language learners and can predict their success in the process of language learning. Considering field dependence/independence cognitive styles, this study aims at determining if they are significant in English vocabulary knowledge. A number of EFL university students took part in the study. The investigation was done through using Vocabulary Size Test (VST) (Nation, 2007) and the Group Embedded Figures Test (GEFT) (Witkin, Oltman, Raskin, and Karp, 1971). Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Findings of Table 3 showed that, there was a significant difference between the test scores of FD (M=8.50, SD=3.23) and FI (M=11.750, SD=3.54) participants, t (78) = 4.28, p=.0.000) and FI participants outperformed the FD group. In line with the findings of Yaghoubi (1994), Salmanian 2001, Luk (2002), Biook and Fathi (2009), Sabet and Mohammadi (2013), Rostampour and Niroomand (2014), Fatemi et al (2014), Hashemian et al (2015), and Khodadady et al (2016), the results of this study also revealed significant differences between FI students' performance as compared to their FD counterparts. As Ahmadi (2002) concluded, our results also showed that FI students tend to use metacognitive strategies, which involve monitoring, planning, and organization, more frequently than their FD counterparts do.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings of Table 3 showed that, there was a significant difference between the test scores of FD (M=8.50, SD=3.23) and FI (M=11.750, SD=3.54) participants, t (78) = 4.28, p=.0.000) and FI participants outperformed the FD group. In line with the findings of Yaghoubi (1994), Salmanian 2001, Luk (2002), Biook and Fathi (2009), Sabet and Mohammadi (2013), Rostampour and Niroomand (2014), Fatemi et al (2014), Hashemian et al (2015), and Khodadady et al (2016), the results of this study also revealed significant differences between FI students' performance as compared to their FD counterparts. As Ahmadi (2002) concluded, our results also showed that FI students tend to use metacognitive strategies, which involve monitoring, planning, and organization, more frequently than their FD counterparts do.…”
Section: Discussionsupporting
confidence: 90%
“…Considering FD/FI cognitive styles, Rostampour and Niroomand (2014) aimed at determining if they are significant in English vocabulary knowledge. Additionally, Hashemian, Jafarpour, and Adibpour (2015) studied the relationships between FI, multiple intelligences, and L2 reading performance among Iranian L2 learners.…”
Section: Cognitive Stylesmentioning
confidence: 99%
“…In view of reading comprehension ability, Salmani-Nodoushan (2006) studied the scores of different types of reading in field-independent and field-dependent learners, and concluded that the learning realization of field-dependent learners was significantly better than that of field-independent learners in terms of judgment, overview and inspiration tasks, while in supplementary sentence question types, field-independent learners performed significantly better than field-dependent learners [28]. Rostampour and Niroomand (2014) tested the correlation between learners' English vocabulary level and cognitive style, and found that there was a highly significant correlation between English vocabulary level and cognitive style in intermediate and advanced learners [29]. In the choice of learning strategies, fewer field-dependent learners will choose social and emotional learning strategies that are more suitable for their own cognitive style [30].…”
Section: The Effect Of Cognitive Style On Language Learningmentioning
confidence: 99%
“…There is an evidence to support the existence of positive and credible relationship between field dependence/independence cognitive styles and vocabulary knowledge (Rostampour and Niroomand, 2014). In a study conducted among Iranian male and female undergraduate EFL learners, a vocabulary size test was administered to divide the students into three groups of high, mid, and low in terms of their vocabulary level.…”
Section: Theory and Practice In Language Studiesmentioning
confidence: 99%